Production and characterization of hydrochars and their application in soil improvement and environmental remediation - Khosravi, Anahita; Zheng, Hao; Liu, Qiang; Hashemi, Masoud; Tang, Yuanzhi; Xing, Baoshan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Hydrochars are rich in carbon, nutrients, and reactive functional groups.•Hydrochar characteristics are determined by HTC conditions and feedstock types.•Hydrochars improve the physical, chemical, and biological property of degraded soil.•Hydrochars containing abundant nutrients could be used as slow release fertilizers.•Hydrochar remediates water and soil pollutions due to its high adsorption capacity. With the rapid global population growth and industrial development, the promotion of sustainable agricultural production and environmental conservation has attracted great public and research interests. Application of carbonaceous materials (e.g., activated carbon, biochar, and hydrochar) for soil improvement and environmental remediation is highly recommended because of their economic viability and applicability. Hydrochars, carbonaceous solid materials with unique physicochemical properties and produced by hydrothermal carbonization (HTC) of biomass, have received wide attention due to their increasing applications as soil amendments, slow-release fertilizers, adsorbents, and energy sources. This review highlights the production of hydrochars from dry and wet feedstocks and summarizes the physicochemical properties including surface structure, porosity, nutrient content, and stability. Applications of hydrochars for soil improvement and environmental remediation are systematically analyzed and reviewed on the aspects of improving soil physicochemical and biological properties, affecting greenhouse gas emission, and remediating heavy metals and organic pollutants in water and soil environments. Finally, the knowledge gaps in the production, characterization, and application of hydrochars are addressed and the future research directions toward the development of hydrochar technology are proposed.